The Conserved Colletotrichum spp. Effector Candidate CEC3 Induces Nuclear Expansion and Cell Death in Plants - Tsushima, Ayako; Narusaka, Mari; Gan, Pamela; Kumakura, Naoyoshi; Hiroyama, Ryoko; Kato, Naoki; Takahashi, Shunji; Takano, Yoshitaka; Narusaka, Yoshihiro; Shirasu, Ken (Frontiers in Microbiology, 2021)
Plant pathogens secrete proteins, known as effectors, that promote infection by manipulating host cells. Members of the phytopathogenic fungal genus Colletotrichum collectively have a broad host range and generally adopt a hemibiotrophic lifestyle that includes an initial biotrophic phase and a later necrotrophic phase. We hypothesized that Colletotrichum fungi use a set of conserved effectors during infection to support the two phases of their hemibiotrophic lifestyle. This study aimed to examine this hypothesis by identifying and characterizing conserved effectors among Colletotrichum fungi. Comparative genomic analyses using genomes of ascomycete fungi with different lifestyles identified seven effector candidates that are conserved across the genus Colletotrichum. Transient expression assays showed that one of these putative conserved effectors, CEC3, induces nuclear expansion and cell death in Nicotiana benthamiana, suggesting that CEC3 is involved in promoting host cell death during infection. Nuclear expansion and cell death induction were commonly observed in CEC3 homologs from four different Colletotrichum species that vary in host specificity. Thus, CEC3 proteins could represent a novel class of core effectors with functional conservation in the genus Colletotrichum.